FRI0078 European Pilot Study on Vitamin D Serum Levels and Disease Activity in Rheumatoid Arthritis Patients. (10th June 2014) - Cutolo, M.; Tincani, A.; Vojinovic, J.; Andreoli, L.; Dall'Ara, F.; Ionescu, R.; Simic-Pasalic, K.; Sefik-Bukilica, M.; Astica, I.; Ferraz, I.; Tlustochowicz, M.; Morovic-Vergles, J.; et al.
Abstract : Background: Several studies have demonstrated low 25(OH)D3 serum levels, which could influence pathogenesis and clinical outcomes of immune-mediated diseases such as rheumatoid arthritis (RA) (1, 2). Objectives: In order to investigate the necessity to implement specific vitamin D patient related outcomes we performed a pilot European multicentre study, involving individuals from different countries/latitudes, to explore 25(OH)D3 serum levels and their possible correlation with disease activity and related outcomes in RA patients during winter season. Methods: We enrolled 270 RA patients (not treated with vitamin D supplementation) and 180 healthy subjects as controls (CNT), from Rheumatology centers in 10 European countries. RA patients mean disease duration was 10±9 years and mean age 56±10 years. Patients informed consent was obtained before collecting blood samples. Complete medical history, health assessment questionnaire (HAQ), rheumatoid arthritis impact disease score (RAID), disease activity scale (DAS28) were recorded. 25(OH)D3 serum levels were evaluated centrally using chemiluminescence immunoassay with an automatic analyser (LIAISON, DiaSorin), and classified as normal (>30 ng/ml), insufficient (between 20 and 30 ng/ml) or deficient (<20 ng/ml) (3). Results: 25(OH)D3 serum levels were significantly lower in RA patients compared to controls (median 16 vs 20 ng/ml) (p<0.0001). In particular, we registered 25(OH)D3 deficiency (<20 ng/ml) in 25% and insufficiency in 70% of RA patients. Male and female RA patients showed similar 25(OH)D3 values (median 19 vs 17 ng/ml) (p=n.s.). We found statistically significant difference in 25(OH)D3 levels between some European countries such as significantly higher 25(OH)D3 serum levels in Spanish RA patients (Canaries Islands) compared to patients from Latvia, Lithuania, Romania, Croatia, Russia and Italy (p<0.01). In agreement with previous observations (4), we found in RA patients statistically significant negative correlations between 25(OH)D3 values and HAQ (r=-0.29, p=0.03), RAID (r=-0.32, p=0.02), and DAS28 scores (r=-0.41, p=0.003), respectively. Conclusions: The results of this multicentre study confirms, at least in winter time, the presence of significantly lower 25(OH)D3 serum levels in RA patients than in healthy control subjects, which seem correlated with disease activity at all latitudes in Europe. The significant negative correlations observed between 25(OH)D3 serum levels and DAS28, HAQ and RAID scores justify the need to develop specific questionnaires for patient reported outcomes (PRO) vitamin D-related, and to validate them in a large European multicentre study. References: 1. Cutolo et al. Autoimmun Rev 2011;11:84-87. Aranow C. J Investig Med. 2011; 59: 881–886. 3. Holick MF. N Engl J Med 2007;357:266-81. 4. Cutolo M. Ann Rheum Dis 2013;72:473-5. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4145